Recent frontiers of climate changes in East Asia at global warming of 1.5°C and 2°C - You, Qinglong; Jiang, Zhihong; Yue, Xu; Guo, Weidong; Liu, Yonggang; Cao, Jian; Li, Wei; Wu, Fangying; Cai, Ziyi; Zhu, Huanhuan; Li, Tim; Liu, Zhengyu; et al. (NPJ climate and atmospheric science, 2022)
East Asia is undergoing significant climate changes and these changes are likely to grow in the future. It is urgent to characterize both the mechanisms controlling climate and the response of the East Asian climate system at global warming of 1.5 and 2 °C above pre-industrial levels (GW1.5 and GW2 hereafter). This study reviews recent studies on East Asian climate change at GW1.5 and GW2. The intensity and variability of the East Asian summer monsoon are expected to increase modestly, accompanied by an enhancement of water vapor transport. Other expected changes include the intensification of the Western Pacific Subtropical High and an intensified and southward shift of the East Asian jet, while the intensity of the East Asian winter monsoon is projected to reduce with high uncertainty. Meanwhile, the frequency of ENSO may increase in a warming world with great uncertainty. Significant warming and wetting occur in East Asia, with more pronounced intensity, frequency, and duration of climate extremes at GW2 than that at GW1.5. The fine structure of regional climate changes and the presence and location of various warming hotspots, however, show substantial divergence among different model simulations. Furthermore, the Asian climate responses can differ substantially between the transient and stabilized GW1.5 and GW2, which has important implications for emission policies. Thus, to better plan effective mitigation and adaptation activities, further research including an in-depth exploration of the divergent responses in transient versus stabilized scenarios, the quantification of future projection uncertainties, and improvements of the methods to reduce model uncertainties are required.